MODEL PEMBELAJARAN DALAM KURIKULUM 2013 PADA MATA PELAJARAN ILMU PENGETAHUAN SOSIAL DI MADRASAH IBTIDAIYAH - Annisa Nidaur Rohmah (PUSAT PENELITIAN DAN PENGABDIAN MASYARAKAT (P3M) SEKOLAH TINGGI ILMU TARBIYAH AL-FATTAH SIMAN LAMONGAN, 2018)
Learning model of 2013 curriculum, which includes Project-Problem Based Learning and Discovery-Inquiry Learning, is assumed to be able to answer the problems occurred in the learning process. This learning model is believed to be able to convey attitudes, knowledge and skills aspects that are in accordance with the objectives of Social Science learning. This study aims to describe the learning model in the 2013 curriculum applied to the Social Science subject, the application of the learning model of 2013 curriculum on Social Science subject, and the impact of applying the learning model in the 2013 curriculum on Social Science subject at MI Negeri Kawistolegi and MI Unggulan Sabilillah Lamongan. This study employs qualitative approach that comprises the study of multisite object. The data collection techniques are observation, interview and documentation. The study uses data analysis technique of Miles and Huberman model which includes data reduction, data presentation, conclusion and cross-site data analysis. To test the data validity, the study uses credibility test with data triangulation. The findings of the study indicate that: 1) The learning model of 2013 curriculum applied to Social Science subject is the learning model Project-Based Learning and Inquiry Learning. 2) The application of the learning model in the 2013 curriculum on Social Science subject covers: a) Planning, b) Implementation, c) Assessment. 3) Impact of Application of 2013 Curriculum Learning Model in Social Science Subject comprises: a) learning model of Project-Based Learning have some impacts such as constructing learners, engaging learners in meaningful task/project, and establishing cooperation in completing the project/task given by teachers, b) learning model of Inquiry learning have some impacts such as having more active learning, developing all existing potentials, orienting on intellectual development, refining creative thinking, fostering curiosity towards an information or knowledge, opening space for discussion, cultivating careful attitude, being meticulous, being cooperative, and being confident.